Contaminant pulse following wildfire is associated with shifts in estuarine benthic communities. (1st January 2023) - Bracewell, Sally A.; Barros, Thayanne L.; Mayer-Pinto, Mariana; Dafforn, Katherine A.; Simpson, Stuart L.; Johnston, Emma L.
Abstract: Novel combinations of climatic conditions due to climate change and prolonged fire seasons have contributed to an increased occurrence of "megafires". Such large-scale fires pose an unknown threat to biodiversity due to the increased extent and severity of burn. Assessments of wildfires often focus on terrestrial ecosystems and effects on aquatic habitats are less documented, particularly in coastal environments. In a novel application of eDNA techniques, we assessed the impacts of the 2019–2020 Australian wildfires on the diversity of estuarine benthic sediment communities in six estuaries in NSW, Australia, before and after the fires. Estuaries differed in area of catchment burnt (0–92%) and amount of vegetative buffer that remained post-fire between burnt areas and waterways. We found greater dissimilarities in the composition and abundance of eukaryotic and bacterial sediment communities in estuaries from burnt catchments with no buffer compared to those with an intact buffer or from unburnt catchments. Shifts in composition in highly burnt catchments were associated with increased concentrations of nutrients, carbon, including fire-derived pyrogenic carbon, and copper, which was representative of multiple highly correlated trace metals. Changes in the relative abundances of certain taxonomic groups, such as sulfate-reducing and nitrifying bacterial groups, in the most impacted estuaries indicate potential consequences for the functioning of sediment communities. These results provide a unique demonstration of the use of eDNA to identify wildfire impacts on ecological communities and emphasize the importance of vegetative buffers in limiting wildfire-associated impacts. Graphical abstract: Image 1 Highlights: Estuarine benthic eukaryotic and bacterial community composition changed post-fire. Greater differences were observed in severely burnt compared to unburnt catchments. Changes were associated with increased sediment py-C, TOC, Cu and nutrients. Shifts in certain bacterial groups may have implications for sediment functioning. EDNA is a useful tool for rapid assessment of wildfire impacts in aquatic systems.